2012
DOI: 10.1139/w2012-031
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing the regulation ofSclerotinia sclerotiorumcutinase A and polygalacturonase 1 during different stages of infection

Abstract: Sclerotinia sclerotiorum releases hydrolytic enzymes that sequentially degrade the plant cuticle, middle lamellae, and primary and secondary cell walls. The cuticle was found to be a barrier to S. sclerotiorum infection, as leaves stripped of epicuticular wax were more rapidly colonized. Consequently, the factors affecting the regulation of genes encoding polygalacturonase 1 (SsPG1) and a newly identified cutinase (SsCUTA) were examined. In vitro, SsCutA transcripts were detected within 1 h postinoculation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Among the genes from the CE family, the gene encoding the cutinase, SsCuta (SS1G_07661), was up-regulated during the early stages of infection (from 1-24 hpi). The induction of SsCuta soon after contact with the leaf surface in the current study agrees with the previous report showing that it was induced upon contact of mycelia with hard surfaces [4] and supports the predicted role of this enzyme in degrading plant cuticle. Additionally, it is not surprising that expression of this gene declined after 24 hpi since host penetration has already been achieved by this time.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Among the genes from the CE family, the gene encoding the cutinase, SsCuta (SS1G_07661), was up-regulated during the early stages of infection (from 1-24 hpi). The induction of SsCuta soon after contact with the leaf surface in the current study agrees with the previous report showing that it was induced upon contact of mycelia with hard surfaces [4] and supports the predicted role of this enzyme in degrading plant cuticle. Additionally, it is not surprising that expression of this gene declined after 24 hpi since host penetration has already been achieved by this time.…”
Section: Resultssupporting
confidence: 93%
“…Li et al [23] reported that SsPG1 expression could be induced by contact with hard surfaces, while Bashi et al [4] reported that SsPG1 , but not SsPG2 , was moderately induced by contact with B. napus leaves and that SsPG1 expression was restricted to the expanding margin of the lesion. They suggested that since SsPG1 expression was also induced by carbon starvation and repressed by galacturonic acid that it may be involved in both early penetration events and lesion expansion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAPKs encoded by SLT2 orthologues in Botrytis cinerea ( BMP3 ) (Rui and Hahn, ), Colletotrichum lagenarium ( MAF1 ) (Kojima et al ., ) and Magnaporthe grisea (MPS1) (Xu et al ., ) are required for germ tube elongation, leading to appressoria formation on solid surfaces and on the host plant. In S. sclerotiorum , hydrolytic enzyme synthesis, in particular the cutinases involved in the degradation of cuticular wax, is also induced by contact with solid surfaces (Bashi et al ., ), and infection ability and trichothecene production have been linked to an SLT2‐like MAPK in Fusarium species (Hou et al ., ; Zhang et al ., ). Taken together, this suggests that, in phytopathogenic fungi, a single MAPK fulfils the role of the SLT2 (cell wall integrity) and SMK1 (spore wall assembly) MAPKs found in yeast, and is involved in the detection of surface integrity, leading to infection structure (appressoria or infection cushions) formation and the deployment of virulence determinants, such as hydrolytic enzymes and toxins, that are required for infection initiation and establishment.…”
Section: Introductionmentioning
confidence: 99%